STAT6 Expression in Solitary Fibrous Tumor and Histologic Mimics: a Single Institution Experience. Issue 4 (April 2020) - Saeed, Omer; Zhang, Shanxiang; Cheng, Liang; Lin, Jingmei; Alruwaii, Fatimah; Chen, Shaoxiong
Abstract : STAT6 stain has proved to be a good surrogate marker for the genetic alteration ( NAB2-STAT6 gene fusion) in solitary fibrous tumor (SFT). This study aims to validate the use of STAT6 rabbit monoclonal antibody in differentiating SFT from its histologic mimics. Forty-five cases of SFT and 110 cases from 9 other spindle cell tumors were collected for STAT6 immunostaining. Positive nuclear STAT6 staining was present in all 45 SFT cases (100% sensitivity). No nuclear staining was identified in other spindle cell neoplasms (0/13, dedifferentiated liposarcoma; 0/17, synovial sarcoma; 0/16, malignant peripheral nerve sheath tumors; 0/25, undifferentiated pleomorphic sarcoma; 0/10, dermatofibrosarcoma protuberans; 0/9, low-grade fibromyxoid sarcoma; 0/6, angiofibroma; 0/5, deep fibromatosis; 0/9, gastrointestinal tumor). The STAT6 staining in SFT was usually diffuse (5+ in 19 cases; 4+ in 17 cases) and strong (40 cases). Monoclonal STAT6 stain is highly sensitive and specific for SFTs and particularly useful in the diagnosis of difficult SFT cases.